ANALISIS ANIMO POLA PENGUNJUNG TERHADAP ASET INTANGIBLE HERITAGE TAMANSARI YOGYAKARTA - Sri Wahyuni; Novi Irawati (Jurnal Manajemen, 2020)
Tourism has become an industry that can enhance the economic growth in Indonesia. As one of the main tourist destinations in Yogyakarta, Yogyakarta has many attractions that can be offered to satisfy the traveler’s need. Recognizing the potential of Tamansari, it is necessary followed by optimizing condition of Tamansari. Development of good visit management concept would optimize the traveler deployment in visiting all the attractions. Visit management is an opportunity to influence the movement of visitors, meet the needs of visitors, encouraging the spread of visits evenly and provide the best travel experience. Keywords: tourism, intangible heritage, asset, visitor management, tourism product